Use of Anti-HIV Immunotoxins as Probes of the Biology of HIV-Infected Cells - SETH H Pincus; Jan McClure; Hua Fang (Canadian Journal of Infectious Diseases)
OBJECTIVE: Anti-human immunodeficiency virus (HIV) immunotoxins are potential treatments for HIV infection. but they may also be used as probes to study the relationship between HIV and the cell it infects. Data from the present study indicate the complexity of this relationship.